193k views
5 votes
I need help showing the work. please help

I need help showing the work. please help-example-1
User Jimbo
by
4.9k points

1 Answer

5 votes

Answer:

see explanation

Explanation:

Using the laws of logarithms

• log x + log y ⇔ log(xy)

• log x - log y ⇔ log (
(x)/(y))

• log
x^(n) ⇔ nlog x

Hence

2
log_(3) x +
log_(3) 2x -
log_(3)(x - 3)

=
log_(3) x² +
log_(3) 2x -
log_(3)(x - 3)

=
log_(3) 2x³ -
log_(3)(x - 3)

=
log_(3)(
(2x^3)/(x-3))

User Matthew Souther
by
6.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.